Development of Learners Worksheet Based Contextual Approach about Organizational System of Life Material for Classroom Learners VII SMP/MTs - Ahmad Supriyadi; Lufri Lufri; Armen Armen (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
The life organization system is one of the learning materials for class VII SMP/MTS students. When making observations with the questionnaire method, it appears that students do not understand the material, this is because students are not invited to associate learning material with students' daily contexts. The contextual approach can be integrated in the form of a Student Worksheet (LKPD). The purpose of developing LKPD based on a contextual approach is expected to make it easier for students to understand the learning material. This type of research is development research using 4-D model with three stages, namely define, design and develop. The define phase is the stage of establishing and defining learning conditions. The design phase is the stage of preparing the LKPD prototype to be developed. The develop stage is the stage of producing LKPD based on a contextual approach and validity testing is done by four validators and practicality tests by two teachers and 30 students of SMP N 13 Padang. The average value of the validity of the Contextual Based LKPD is 82% with valid criteria. The average value of the practice by teacher is 83% with practical criteria. The average value of the practice carried out by students is 88% with practical criteria. This it was concluded that LKPD based on the contextual approach developed had valid and practical criteria.